Reimagining Malaysia - Yeo, Bee Yin (Democratic Action Party, 2018)
This generation of Malaysians needs to dream again for our country. We need to reimagine a Malaysia that is above and beyond what we can see today. We need re-imagination to rebuild this country. In this book, I share my insights as a young lawmaker from different aspects of nation-building that are close to my heart - institutional reform, education, youth, women, sustainable development and the weaker members of society - in terms of where we are now and what I think we can achieve in the future. Being a lawmaker of Selangor, which is a state governed by the federal opposition, gives me a different perspective on these issues, both as a member of the government as well as the opposition. I also share some of my personal stories in the book to put into context the convictions, hopes and dreams I have for my beloved nation.